Studies on PEMA based solid polymer electrolytes - Amir, Shahrul; Mohamed, Nor Sabirin; Subban, Ri Hanum Yahaya (Trans Tech Publications, 2010)
Solid polymer electrolytes comprising of various weight ratios of poly(ethyl methacrylate) (PEMA) and lithium perchlorate (LiClO4) salt were prepared via solution casting technique using N,N-Dimethylformamide (DMF) as the solvent. The conductivity values of the electrolytes were determined utilizing Solatron 1260. The highest conductivity obtained is in the order of 10-6 S cm-1. Structural properties of the electrolytes were investigated by X-ray diffraction and the results show that the highest conducting film is the most amorphous.